Sosialisasi Tata Cara Penyembelihan Dan Penyaluran Hewan Qurban Sesuai Syariat Islam - Suparman, Yogi; Saputra, Adha; Oki, Alber; Hidayat, Tatang; Tsauri, Sidiq Samsi (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2023)
Slaughtering sacrificial animals is a great and special act of worship performed by Muslims on Eid al-Adha. The procedure and process of this slaughter must be based on the provisions of Islamic law. So that the main reference in the implementation of this service is the Al-Quran and saheeh prophetic traditions. The purpose of this community service event is to socialize the procedures for slaughtering qurban animals according to the Al-Quran and hadith to Muslims who live in the STIQ ZAD Campus area; so that their qurban worship is valid and accepted in the sight of Allah. The method of implementing this service is in two ways, namely the delivery of material (theory) and direct practice. The results of this community service are: First, the delivery of material on how to slaughter qurban animals runs smoothly. Second, the process of practicing slaughtering qurban animals is in accordance with Islamic law. Third, the distribution of qurban animals to the community runs without obstacles and gets a positive response from the Muslim community in the STIQ ZAD Campus area, Cianjur.